The The Effect of Return On Assets, Debt to Equity Ratio dan Earnings Per Share on Stock Return in the Telecommunications Sector - Qori Fadhilah; Aswin Akbar (PT Mattawang Mediatama Solution, 2024)
This study aims to examine and analyze the effect of return on assets, debt to equity ratio and earnings per share on the share price of telecommunications sector companies listed on the Indonesia Stock Exchange. This research uses secondary data, secondary data in this study is obtained from the annual financial statements of companies listed on the Indonesia Stock Exchange by accessing the www.idx.co.id website. The sample in this study was 6 companies, sampling using purposive sampling techniques. The method used in this study is quantitative descriptive method. The data analysis method in this study used panel data, namely Eviews 12. This research was conducted based on data obtained during the period 2014 to 2023. The results of this study show that partial return on assets has no effect on stock returns, partial debt to equity ratio has no effect on stock returns and partial earnings per share has no effect on stock returns. Simultaneously return on assets, debt to equity ratio and earnings per share have no effect.